PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN BEBAN KERJA TERHADAP LOYALITAS KARYAWAN MELALUI KEPUASAN KERJA ( Studi Kasus Pada Karyawan PT. Kawasan Berikat Nusantara Persero Jakarta) - Adhitia Pratama; Sri Suryoko; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
Businnes competition now demanding companies to have competitive employee in many aspects. The availability of company to compensate their employee, to establish pleasant working environment, and ability to allocating workload fairly are factors which is make employee stay longer working in the company and give a satisfaction feeling in every job they done. The objective of this research is to measure the influence of compensation, working environment, and workload to employee loyality through work satisfaction. Data accumulation using interview techniquie by questionnaire instrument. The data analyze using qualitative and quantitative using coefficient determination test, simple and double linear regretion, cross table, significant test, path analysis, and trimming.The result of this research showing corelation of compenasation to working satisfactory strongly with correlation number 0,715. Coefficient determination (R2) of working environment to working satisfactory 46,9%. The result of path analyzing workload to working satisfactory have 0,268 and have to be proceed by trimming (exluding process of eksogen variable which have insignifacant number). Simultaneously compensation, working environment, workload, and working satisfaction have significant influences to employee loyality with F count > F table (13,972 > 2,487) with significant number 0,000 < 0,005.